A review of spare parts supply chain management - Zineb Achetoui; Charif Mabrouki; Ahmed Mousrij (Jurnal Sistem dan Manajemen Industri, 2019)
The particular characteristics of spare parts have prompted several authors to provide substantial results for effective spare parts supply chain management. In this context, the purpose of this paper is to present the significant contributions that researchers have proposed, over time, for the spare parts supply chain management. The literature has shown that the particular characteristics of spare parts have a significant impact on inventory performance and customer demand fulfillment. For this reason, most of the contributions were focused on spare parts classification methods, forecasting methods and inventory optimization.  The focus of researchers on some areas of spare parts management allowed us to identify some promising perspectives that were not developed in the literature, such as the development of performance measurement frameworks for the spare parts supply chain and the measurement of organizational maturity.